PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 020 PADANG MUTUNG - Nuriman '; Hendri Marhadi; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This Research of background by in reality result of learning IPS Class student of IV SD Country 020 Field of Mutung still not yet shown satisfying value. Intention of this research is to improve result learn IPS Class student of IV SD Country 020 Field of Mutung District of Camphor with applying of model study of type co-operative of Numbered Head Together (NHT). This Research is research of executed class action at Student Class of IV SD Country 020 Field of Mutung District Of Camphor Sub-Province Camphor Province of Riau. Instrument Research consist of Peripheral of used Study at this research of berpedoman at Curriculum Mount Set of Education (KTSP) or which is recognized with Curriculum 2006. Peripheral of study consist of syllabus, RPP, student spread sheet and perception sheet. At first meeting of cycle to I teacher activity reside in at classification